CORPUS EPOCHALIS. MYSTICISM, BODY, HISTORY - Mihailescu, Calin (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1991)
The discourse of the body and history in the mystical tradition, especially Pascal. De Certeau on the history of Mysticism, Deleuze and Guattari on the body.